2012
DOI: 10.1021/bm201813s
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of O-Glycopolypeptide Polymers and Their Molecular Recognition by Lectins

Abstract: The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 61 publications
(97 reference statements)
0
85
0
1
Order By: Relevance
“…65 They investigated the selective binding of the poly(a-manno-O-lys) with the lectin ConA using precipitation, hemagglutination assays, and isothermal titration calorimetry (ITC). 66 To investigate the secondary structure effects on the binding affinity, they also prepared racemic D,L-glycopolypeptides, and found that there is no significant difference in binding affinity between helical L-glycopolypeptide and racglycopolypeptide with random coil conformation. The ITC analysis also showed that the binding process is enthalpy driven for both a-helical and random coil structures.…”
Section: Biomolecule Responsive Polypeptidesmentioning
confidence: 99%
“…65 They investigated the selective binding of the poly(a-manno-O-lys) with the lectin ConA using precipitation, hemagglutination assays, and isothermal titration calorimetry (ITC). 66 To investigate the secondary structure effects on the binding affinity, they also prepared racemic D,L-glycopolypeptides, and found that there is no significant difference in binding affinity between helical L-glycopolypeptide and racglycopolypeptide with random coil conformation. The ITC analysis also showed that the binding process is enthalpy driven for both a-helical and random coil structures.…”
Section: Biomolecule Responsive Polypeptidesmentioning
confidence: 99%
“…In a later report, Gupta and coworkers polymerized the same carbamate linked glycosylated lysine NCAs, as well as racemic and lactosylated versions, using acetate protecting groups instead of the previously reported benzoyl groups. 117 Polymerizations were again initiated with an amino terminal PEG in the presence of "proton sponge" in dioxane, but with acetate protecting groups these monomers gave molecular weights closer to theoretical values. Control over glycopolypeptide length was not demonstrated; however, narrow molecular weight distributions and degrees of polymerization from 35 to 64 were reported.…”
Section: Polymerization Of Glycosylated Monomersmentioning
confidence: 95%
“…Changing the glycan moiety shown to change antibacterial activity (Talat et al, 2011) O-Glycosylated lysine-Ncarboxyanhydride monomers TOF (DHB) For synthesis of O-glycopolypeptide polymers (Pati et al, 2012b) Glycosylated MUC6 glycoprotein…”
Section: Tof/tof (Chca) Esimentioning
confidence: 99%